Sequential determination of nickel and cadmium in tobacco, molasses and refill solutions for e-cigarettes samples by molecular fluorescence - Talio, María Carolina (2017)
In this work, a new procedure was developed for separation and preconcentration of nickel(II) and cadmium(II) in several and varied tobacco samples. Tobacco samples were selected considering the main products consumed by segments of the population, in particular the age (youth) and lifestyle of the consumer. To guarantee representative samples, a randomized strategy of sampling was used. In the first step, a chemofiltration on nylon membrane is carried out employing eosin (Eo) and carbon nanotubes dispersed in sodium dodecylsulfate (SDS) solution (phosphate buffer pH 7). In this condition, Ni(II) was selectively retained on the solid support. After that, the filtrate liquid with Cd(II) was re-conditioned with acetic acid /acetate buffer solution (pH 5) and followed by detection. A spectrofluorimetric determination of both metals was carried out, on the solid support and the filtered aqueous solution, for Ni(II) and Cd(II), respectively. The solid surface fluorescence (SSF) determination was performed at λem = 545 nm (λex = 515 nm) for Ni(II)-Eo complex and the fluorescence of Cd(II)-Eo was quantified in aqueous solution using λem = 565 nm (λex = 540 nm). The calibration graphs resulted linear in a range of 0.058–29.35 μg L−1 for Ni(II) and 0.124–56.20 μg L−1 for Cd(II), with detection limits of 0.019 and 0.041 μg L−1 (S/N = 3). The developed methodology shows good sensitivity and adequate selectivity, and it was successfully applied to the determination of trace amounts of nickel and cadmium present in tobacco samples (refill solutions for e-cigarettes, snuff used in narguille (molasses) and traditional tobacco) with satisfactory results. The new methodology was validated by ICP-MS with adequate agreement. The proposed methodology represents a novel fluorescence application to Ni(II) and Cd(II) quantification with sensitivity and accuracy similar to atomic spectroscopies, introducing for the first time the quenching effect on SSF.